Pelaksanaan Kelas Ibu Hamil Sebagai Upaya Peningkatan Pengetahuan Ibu, Keluarga Dan Kader Dalam Deteksi Dini Resiko Tinggi Ibu Hamil Di Wilayah Kerja Puskesmas Sambeng Kabupaten Lamongan - Muhith, Abdul; Fardiansyah, Arief; Y, Asih Media; Larasati, Yenny (Universitas Tribhuwana Tunggadewi, 2019)
The introduction of high risk pregnant women is done through early detection of risk factors pro actively in all pregnant women by mother, family, and cadres. The program organized by the Ministry of Health to support the step is the Pregnant Women's Class. The purpose of this study is to improve knowledge of mother, family and cadres in early detection of high risk pregnant women in the working area of Sambeng Community Health Center of Lamongan. The design of this research is Quasi Experiment with Pre-Post Design approach. Its population is pregnant mother, family and cadres who attend class of pregnant mother in working area of UPT Sambeng Public Health Center. Sampling technique used was Purposive sampling, got 40 respondents of pregnant women, 40 families and 20 cadres. Data were analyzed with Wilcoxon Signed Ranks Test. Wilcoxon Signed Ranks Test results show that there is influence of maternal class implementation with knowledge of mother (Z value = -4,815), family (Z value = -4,315) and cadre (Z value = -3,162) in early detection of high risk pregnant women. The success of pregnant women's classes can be continued by using innovative and attractive media such as simulation and movie viewing to be more engaging for the community, and families to participate, thus encouraging people to do early detection.